PELAKSANAAN PROGRAM PEMBANGUNAN RUMAH SEDERHANA LAYAK HUNI PADA BADAN PEMERDAYAAN MASYARAKAT DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Lily Sarvini; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Implementation of simple livable home development program is support program from government to poor society, left behind and located in improvement residential quality area. The aim of the program is to improve and provide society bacis infrastructure needs, in village which implemented through public empowerment system but in the implementation of simple livable home development happen irregularity that is caused of lack in controlling in impelemtation of simple livable home development.The theory concept that used is implementation. For analyzing in impelentation of simple livable home development in Bagan Sinembah village Rokan Hilir regency, researcher used theory George R. Terry. The researcher aims to know the implementation of simple livable home development simple livable home development in Bagan Sinembah village Rokan Hilir regency. The researcher uses qualitative research with descriptive method. In collecting data, researcher uses key informant as information source and triangulasi technique as source in data validity test.The result of research shows that implementation of simple livable home development is not suitable with the regulation which mean happen irregularity in implementation of simple livable home development in Bagan Sinembah village Rokan Hilir regency which included planning, organizing, implementation and controlling need support by all of administrator as well as relevant authorities in order to the better implementation of simple livable home development in the future.Key Words : Implementation, Simple Livable Home Development, Public Empowerment